DETERMINANTS OF EMPLOYEE EMPOWERMENT: THE CONTRIBUTION OF LEADERSHIP ROLES THROUGH GHRM MANAGEMENT - Siti Rafika Arman; Abdul Haeba Ramli; Lia Amalia; Ferryal Abadi (POLITEKNIK LP3I JAKARTA, 2026)
The phenomenon of climate change that impacts environmental issues triggers organizations globally to strengthen environmental protection as result of their business activities. In motivating environmental protection actions, the contribution of empowered employees in their environmentally friendly practices is inseparable. This study aims to explore the relationship between organizational encouragement of Top Management Green Commitment (TMGC) and Green Transformational Leadership (GTL) on the management of Green Human Resource Management (GHRM) so that it has implications for Green Employee Empowerment (GEE). Data collection in this study was designed using a survey method by distributing online questionnaires to 480 respondents working in the digital industry and startup companies. Research responses were taken using a non-probability sampling method with a purposive sampling approach. This research is quantitative with data processing of relationships between variables using the Structural Equation Model (SEM) method. The study found that GTL and GHRM have a significant influence on GEE behavior. This study also confirmed the relationship between TMGC and GHRM practices does not significantly affect GHRM practices. This shows that top management commitment alone without any examples and real actions is not enough to influence individual behavior to play an active role in implementing sustainability within the organization.